2015
DOI: 10.4236/ajac.2015.613100
|View full text |Cite
|
Sign up to set email alerts
|

Stability Indicating RP-HPLC Method for Estimation of Impurities of Vitamin D<sub>3</sub> Analogue and Corticosteroid Used as Antipsoriatic Drugs. An Attempt to Characterize Pre-Calcipotriene

Abstract: A single RP-HPLC method is developed for estimation of isomeric impurities of vitamin D3 analogueCalcipotriol/Calcipotriene (Calci) and impurities of Betamethasone dipropionate (BD). The developed method is capable of separating impurities of Calci and BD, specifically pre-Calcipotriene (Pre-Calci) from other known and unknown impurities. Pre-Calci is isolated and is characterised using few analytical techniques. These impurities are separated using a RP-C18 150 × 4.6 mm, 2.7 µm column maintained at 50˚C. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The peaks at 1058 and 1017 cm –1 were attributed to the C–O stretch. These findings are in agreement with the literature …”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The peaks at 1058 and 1017 cm –1 were attributed to the C–O stretch. These findings are in agreement with the literature …”
Section: Resultssupporting
confidence: 94%
“…The drug content of the lyophilized CPM NSs was 0.36 ± 0.02 w/w, which equates to a percentage recovery of 87.02 ± 4.32% w/w (Table ). Drug loss could occur because some drugs may be attached to the milling beads during the filtering process . After 3 months, there was no significant difference in the drug content of the lyophilized CPM NSs ( p = 0.8593), indicating that they can be stored for up to 3 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Survey on the literature reveals that few approaches were described for the determination of doxercalciferol and several studies present on the extraction of vitamin D from human blood samples, plasma, placebo etc. Few assay methods were also reported for vitamin D analogs [27][28][29][30][31][32][33][34][35] including the quantification of doxercalciferol degradation components by RP-HPLC and solid-phase extraction. In that study, the chromatographic parameters utilized for the estimation of doxercalciferol degradants/impurities with infusion volume 100 µL, the flow rate of 1.60 mL/min, water and acetonitrile are utilized as mobile solvent at a column temperature of 40 o C. 36 A doxercalciferol related substance technique is reported in United States Pharmacopoeia (USP) with specified impurities.…”
Section: Introductionmentioning
confidence: 99%
“…However, the comprehensive literature review found that very few methods were reported for the determination of related substances 23-26, degradation products [27][28] and metabolites [29][30][31][32] of cholecalciferol. The methods that have been reported for related substances involve normal phase chromatography 23, qualitative and comparative study using two new stationary phases 24, Estimation of Impurities of Vitamin D3 Analogue and not impurities of Vitamin D3 25 and related substances by LC-MS method 26. Degradation & metabolites studies reported by LC-MS methods 27-32. None of the above methods discussed pertaining to the stability indicating nature, the degradation kinetics of the product and degradant impurities profiling which is the essential regulatory pharmaceutical requirement of the various countries for the therapeutic efficacy and safety of the pharmaceutical dosage form. The LC-MS methods involve a higher cost per sample analysis than the reverse-phase chromatography method.…”
Section: Introductionmentioning
confidence: 99%